2021
DOI: 10.1002/prot.26083
|View full text |Cite
|
Sign up to set email alerts
|

Insights into modular polyketide synthase loops aided by repetitive sequences

Abstract: The loops of modular polyketide synthases (PKSs) serve diverse functions but are largely uncharacterized. They frequently contain amino acid repeats resulting from genetic events such as slipped‐strand mispairing. Determining the tolerance of loops to amino acid changes would aid in understanding and engineering these multidomain molecule factories. Here, tandem repeats in the DNA encoding 949 modules within 129 cis‐acyltransferase PKSs were cataloged, and the locations of the corresponding amino acids within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…However, the side chains of M327, D328 and E421 are not involved in co-factor binding and likely contribute directly to the interface with the PksJ ACP4 domain. These mutagenesis experiments suggested that the masking pattern observed in the carbene footprinting experiments is consistent with docking of the PksJ ACP4 domain at the KR C subdomain site, and the additional masking occurred as a result of the 24-residue linker region extending across the KR domain surface, 42 as depicted in Fig. 3B .…”
Section: Resultssupporting
confidence: 68%
“…However, the side chains of M327, D328 and E421 are not involved in co-factor binding and likely contribute directly to the interface with the PksJ ACP4 domain. These mutagenesis experiments suggested that the masking pattern observed in the carbene footprinting experiments is consistent with docking of the PksJ ACP4 domain at the KR C subdomain site, and the additional masking occurred as a result of the 24-residue linker region extending across the KR domain surface, 42 as depicted in Fig. 3B .…”
Section: Resultssupporting
confidence: 68%
“…In case these interfaces vary between PKS’s expressed by different organisms, only sequences from characterized streptomyces PKS’s were employed 9 . Analysis of the first 2 interfaces was aided by sequence logos constructed using 186 γ-modules not split by docking domains from 63 synthases 29,31 . Analysis of the third was aided by sequence logos constructed using 91 γ-modules split by Class 1a docking domains from 64 synthases 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the first 2 interfaces was aided by sequence logos constructed using 186 g-modules not split by docking domains from 63 synthases 29,31 . Analysis of the third was aided by sequence logos constructed using 91 g-modules split by Class 1a docking domains from 64 synthases 29 .…”
Section: Interfacesmentioning
confidence: 99%
“…KSs from 129 characterized PKSs were grouped based on the chemistries at the α-, β-, and γ-carbons of the substrates they accept, as predicted from biosynthetic models of each PKS and sequence analysis of KRs and ERs (Supporting Information and Source Data 1). , A cladogram of these KSs was generated, revealing significant clustering of KSs that accept less common substrates (nomenclature for KSs explained in Experimental Procedures and Table S1) (Figure ). KSs collaborating with upstream nonribosomal peptide synthetase (NRPS) domains are distinct, as has been noted in both cis - and trans -AT assembly lines (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…As in a previous study, they were named by the polypeptide in which the KS-containing module starts, the number of the module within that polypeptide, and the α–δ (a–d, or z for all others) architecture of the module (Supporting Information and Table S1). To focus on the gatekeeping logic employed by PKSs primarily from actinomycetes, 233 KSs were excluded from the analysis (Figures and S1–S3). The remaining 739 KSs from 92 assembly lines were sorted into families and groups (Figures and S4).…”
Section: Methodsmentioning
confidence: 99%